Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/c9ta13452b
|View full text |Cite
|
Sign up to set email alerts
|

A graphene oxide–molecular Cu porphyrin-integrated BiVO4 photoanode for improved photoelectrochemical water oxidation performance

Abstract: Monoclinic bismuth vanadate (BiVO4), as a rising star in light-catching materials, has been researched in many fields, such as photoelectrochemical water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 45 publications
3
47
0
Order By: Relevance
“…The O 1s spectrum is deconvoluted into three peaks of 529.5 eV, 530.8 eV, and 531.7 eV, which are assigned to O 2− , OH − , and the bound water (H−O−H), respectively (Figure 1c). The area ratio of OH − to O 2− is close to the theoretical ratio for hydroxide, confirming the presence of FeOOH [16] . Based on the XPS and ATR−FTIR analysis, FeOOH and molecular catalyst Ru(bda)(vpy) were successfully immobilized on the surface of Fe 2 O 3 .…”
Section: Methodssupporting
confidence: 71%
“…The O 1s spectrum is deconvoluted into three peaks of 529.5 eV, 530.8 eV, and 531.7 eV, which are assigned to O 2− , OH − , and the bound water (H−O−H), respectively (Figure 1c). The area ratio of OH − to O 2− is close to the theoretical ratio for hydroxide, confirming the presence of FeOOH [16] . Based on the XPS and ATR−FTIR analysis, FeOOH and molecular catalyst Ru(bda)(vpy) were successfully immobilized on the surface of Fe 2 O 3 .…”
Section: Methodssupporting
confidence: 71%
“…[255] Through density functional theory calculations and experimental studies, it showed that the doping of Fe atoms into the lattice of CoO x produced abundant oxygen vacancies, which significantly improved the interfacial hole injection property of BiVO 4 and reduced the OER onset potential (Figure 19d). Recently, many other advanced co-catalysts have been demonstrated with outstanding performance and stability, such as natural polyphenols/Fe ion, [256] Cu porphyrin, [257] Fe-based (Ni 1−x Fe x and Co 1−x Fe x ) layered double hydroxide, [258][259][260][261] InPO x , [86] molecular Co Cubane, [262] MnO 2 , [263][264][265] and Co 8 -polyoxometalates. [266] In Table 4, it can be seen that by modifying pristine semiconductors with co-catalyst, boosted PEC performance can be achieved due to the significantly enhanced interfacial hole-injection efficiency.…”
Section: Co-catalyst Developmentmentioning
confidence: 99%
“…However, they typically lose the ability to catalyze decomposition of water into O 2 and H 2 as a result of the downward shift of their conduction band edge, consisting of a d‐orbital, where the evolution of H 2 from H + is expected to occur [13–15] . Bismuth vanadium oxide (BiVO 4 ) is a type of metal oxide, which has been applied as a photoanode for the evolution of O 2 from water [16–20] . Hence, in the prototype comprising a BiVO 4 photoanode (cf.…”
Section: Introductionmentioning
confidence: 99%